2018
DOI: 10.1002/pamm.201800156
|View full text |Cite
|
Sign up to set email alerts
|

On a least‐squares finite element formulation for sea ice dynamics

Abstract: In this contribution a mixed least-squares finite element method (LSFEM) for the modeling of sea ice motion including a viscous-plastic (VP) sea ice rheology is investigated. The simulation of sea ice motion goes back to the findings in Hibler III [4], where a numerical model for the simulation of sea ice circulation and thickness evolution over a seasonal cycle is introduced. Both the ice thickness and ice concentration distribution are explicitly described on the basis of evolution equations. Recent research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Previous studies on the implementation of the sea ice model have shown that the LSFEM is a promising solution to the numerically stiff problem, cf. [24] and [21]. The resolution of the large gradients in the viscosity function, which can be characterized as localization effects, has to be investigated for convergent meshes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the implementation of the sea ice model have shown that the LSFEM is a promising solution to the numerically stiff problem, cf. [24] and [21]. The resolution of the large gradients in the viscosity function, which can be characterized as localization effects, has to be investigated for convergent meshes.…”
Section: Discussionmentioning
confidence: 99%
“…The time-dependent values of the tracer equations need to be discretized with a suitable time integration scheme. In previous investigations different time integration schemes are elaborated, such as the higher-order Taylor-least-squares scheme based on [22], see [21], and the well known Backward-Euler and Crank-Nicolson schemes, compare to [24] and [21]. In the case of the Taylor-least-squares time integration, higher continuity requirements are imposed on the tracer quantities.…”
Section: Time Discretizationmentioning
confidence: 99%